Towards a Reference Architecture for Augmentative and Alternative Communication Systems - Franco, Natália M.; Silva, Edson A.; Lima, Rinaldo J.; Fidalgo, Robson N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2018: Anais do XXIX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2018.1073, 2018)
Augmentative and Alternative Communication (AAC) systems are broadly used to expand communication skills of individuals with severe communicative disorders. These systems should prioritize requirements that contribute to making the communication easy and effective to be robust. However, there is no guideline available to aid the implementation of these systems. In this paper, we analyze the fragmented knowledge available on scientific proposals and technological solutions to extract key concepts for a robust AAC system. Then, we propose a Reference Architecture (RA) that can be used as a conceptual guide to define and evaluate concrete and robust software architectures for several goals including literacy in inclusive education.